Research and Development for Sustainable Participatory Forest Management - Jha, Mohan (Indian Forester, 2007)
This paper deals with some aspects of the research needs of JFM to provide sustainability. Research needs of JFM can be broadly categorised in to the forestry related research and socio-economic research. It is important to focus research on multi-tier forestry to meet the needs of JFM. There is need to reorient the Silvicultural Systems and define the productive parameters for new alternatives which will blend these NTFPs with timber and fuelwood. Research on different models for the optimum returns and providing protection to the soil and biodiversity is a priority area. Forest research on Utilization aspect will provide the sustainability and the required financial return to the community and the state in long run. More focussed research is needed on grasslands and fodder to meet specific needs of JFM. Impact of JFM on the socio-economic aspects of the local community is important for sustainability. Participatory approach requires understanding of factors influencing the involvement of local people and long-term sustainability. It becomes imperative to develop performance indicators.